Tandem occlusions involving the internal carotid and anterior cerebral arteries—A rare form of stroke: Results from the multicenter EVATRISP collaboration study - Filioglo, Andrei; Simaan, Naaem; Honig, Asaf; Heldner, Mirjam; Pezzini, Alessandro; Martinez-Majander, Nicolas; Padjen, Visnja; Baumgartner, Philipp; Papanagiotou, Panagiotis; Salerno, Alexander; Nolte, Christian; Nordanstig, Annika; et al. (Frontiers in Neurology, 2022)
Abstract: Background: Patients with stroke secondary to isolated anterior cerebral artery (ACA) occlusions have poor outcomes. Whether tandem occlusions (TO) of the extracranial internal carotid (ICA) and the ACA carries even worse outcomes remains unknown. Methods: Patients with TO involving ICA and ACA occlusions were identified from 14 participating centers from the EndoVascular treatment And ThRombolysis in Ischemic Stroke Patients (EVATRISP) project which is a multicenter, observational, cohort study with prospective accrual of data followed by retrospective data analysis. Patients with isolated ACA stroke served as controls. Results: Included were 92 patients with isolated ACA and 16 patients with ICA-ACA TO stroke. On univariate analyses, patients with TO had more severe strokes on admission (median NIHSS [IQR] 13.5 [9-21] vs. 8 [5-12], p=0.003) and were more often treated with thrombectomy (81% vs. 40%, p=0.002). Mortality rates were higher among TO patients (31% vs. 11%, p=0.03). Rates of favorable functional outcomes were numerically lower among TO patients (38% vs 60%) but the difference was not statistically significant (p=0.09). On multivariate analyses, the presence of TO did not modify the chances for favorable outcomes. Conclusion: TO stroke with ICA and isolated ACA involvement is rare and results in more severe initial neurological deficits and higher mortality compared to those seen in patients with isolated ACA stroke.